Meta-Analysis the Effect of School Based Intervention on Smoking in Adolescents - Muhammad Rifqi Azhary; Eti Poncorini Pamungkasari; Yulia Lanti Retno Dewi (Journal of Health Promotion and Behavior, 2021)
Background: Tobacco is a global problem, in which at least 5 million people die from diseases caused by the consumption of tobacco products such as cigarettes each year, such as cervical cancer, heart disease, gastric ulcers, tuberculosis, kidney failure, pancreas, leukemia, pneumonia, gum and mouth disease as well as lung cancer. This study aims to estimate the magnitude of the effect of School based intervention on cigarette consumption based on the results of a number of previous studies.Subjects and Method: This research is a systematic study and meta-analysis, with PICO as follows Population = junior high school and high school students, Intervention = School based intervention. Comparison = No School based intervention. Outcome = cigarette consumption. The articles used in this study were obtained from several databases including PubMed, ScienceDirect and Google Scholar. This article article was collected for 2 months. The keywords for searching articles are as follows: "School-based intervention" AND tobacco OR smoke OR cigarette AND RCT OR "Randomized Controlled Trial". The articles included in this study are full text articles with a randomized controlled trial study design. Articles were collected using PRISMA flow diagrams. They were analyzed using the Review Manager 5.3 application.Results: A total of 11 articles reviewed in this meta-analysis study originated from the United States, Sweden, California, Brazil, Germany, Ireland, China, Australia and Indonesia. Studies show that School based intervention has no significant effect on cigarette consumption (Standardized Mean Difference = -0.74; 95% CI = -1.67 to 0.18; p = 0.110).Conclusion: School based intervention reduces cigarette consumption.Keywords: School based intervention, tobacco, cigarette consumptionCorrespondence: Muhammad Rifqi Azhary. Masters Program In Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: Rifqiazhary.ra@gmail.com.Journal of Health Promotion and Behavior (2021), 06(01): 32-44https://doi.org/10.26911/thejhpb.2021.06.01.04